The story of Cirrus Flux - Skelton, Matthew 1971- (Delacorte Press, 2009)
In 1783 London, the destiny of an orphaned boy and girl becomes intertwined as the boy, Cirrus Flux, is pursued by a sinister woman mesmerized, a tiny man with an all-seeing eye, and a skull-collecting scoundrel, all of whom believe that he possesses an orb containing a divine power